Variation of Syntax Errors and Causative Factors in Motivational Essays for Writing Training Participants - Ilmatus Sa’diyah (Future Science, 2022)
Errors in writing in Indonesian made by writing training participants have indeed become a characteristic. This is because the trainees have just learned how to write in Indonesian properly and correctly. Therefore, syntactic error analysis needs to be done to identify variations of errors and the causes of errors made by writing trainees. The analysis was conducted to improve the quality of writing training for trainees in terms of providing training materials. The analysis was carried out using a descriptive analysis method on eight articles of training participants. The forms of errors identified in the writing of the writing training participants included the use of conjunctions, sentence order, use of question words, sentence pattern errors, and completeness of sentence structure. Overall, the most dominant error was the trainee's writing error in using conjunctions. Meanwhile, the cause of the error occurred because the trainees did not know how to write sentences in Indonesian correctly and according to Indonesian rules.